2016
DOI: 10.1149/2.0291702jes
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Localized Corrosion of Ferritic Stainless Steels by Using the Liquid-Phase Ion Gun Technique

Abstract: The initiation of localized corrosion of types 430 and 443J1 ferritic stainless steels was evaluated in 0.15 mol dm −3 Na 2 SO 4 solution. A liquid-phase ion gun (LPIG), a silver microelectrode covered with a silver chloride layer, was cathodically polarized to generate Cl − in the vicinity of the stainless steel polarized at 0.4 V SSE . Contact of the stainless steel surface with the Cl − -concentrated environment by the LPIG operation induced a rapid increase in anodic current flow through the stainless stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Various researchers have approached to explore the growth kinetics and the electronic properties of the passive lm with a stable condition in the alkaline buffer solution. [12][13][14] All the electrochemical measurements were carried out in a boricborate buffer solution (0.15 mol dm −3 H 3 BO 3 and 0.15 mol dm −3 NaB 4 O 7 ), with pH 8.4, purged with 99.999% N 2 gas for 1 h at room temperature. In all electrochemical tests, the reproducibility was examined at least three times with different specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Various researchers have approached to explore the growth kinetics and the electronic properties of the passive lm with a stable condition in the alkaline buffer solution. [12][13][14] All the electrochemical measurements were carried out in a boricborate buffer solution (0.15 mol dm −3 H 3 BO 3 and 0.15 mol dm −3 NaB 4 O 7 ), with pH 8.4, purged with 99.999% N 2 gas for 1 h at room temperature. In all electrochemical tests, the reproducibility was examined at least three times with different specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Most often, studies of alloy corrosion have focused on Cl – species due to their well-known role in accelerating the decomposition of the passivating oxide film, and thereby initiating corrosion. Three models have been proposed for oxide layer breakdown in the presence of halides, namely, (1) the adsorption model, , in which adsorbed halides form a metal cation complex within the oxide layer, which accelerates film removal, (2) the penetration model, , in which the penetration of halides results in the formation of conductive pathways within the oxide film that facilitate the transfer of metal cations from the surface into the bulk, and (3) the film breakdown model, , which suggests that the presence of adsorbed halides decreases the surface tension of the oxide, resulting in its mechanical rupture. These mechanisms are, however, applicable for systems involving a halide ion and a well-oxidized substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is KOH because the K + ion has a smaller charge density compared to Li + and therefore, it exhibits a lower affinity for the negatively charged – OH ion, , making water chemistry control more manageable. Moreover, KOH is substantially (at least 5 times) cheaper than LiOH and can be sourced much more readily than nuclear-grade Li-hydroxide. As such, the use of KOH as compared to LiOH would result in substantial reductions in plant operational costs.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported the presence of Fe and Cr in the passive film formed on FeCrNi alloy in acidic aqueous solutions, while a detailed content between Fe and Cr in the film is different. On one hand, it has been reported that the outermost layer of passive film becomes enriched with Fe cations, while Cr are concentrated as cations near the metal‐passive film interface . Conversely, some studies have shown that the Cr is more concentrated across the entire passive film than Fe .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some studies have shown that the Cr is more concentrated across the entire passive film than Fe . The film composition varies with substrate alloy composition and passivation conditions such as solution temperature, pH, anions concentration, and passivation potential, which is related to the film's electrochemical behavior . It is important to investigate the composition of passive film formed on FeCrNi alloys under a particular corrosive condition.…”
Section: Introductionmentioning
confidence: 99%